Spatial–Temporal Evolution of the Coupling Coordination Degree between Water and Land Resources Matching and Cultivated Land Use Eco-Efficiency: A Case Study of the Major Grain-Producing Areas in the Middle and Lower Reaches of the Yangtze River - Zhenggen Fan; Qingqing Luo; Hu Yu; Ji Liu; Wentong Xia (Land, 2023)
Improving the coupling coordination degree between water and land resources matching (WLRM) and cultivated land use eco-efficiency (CLUE) is crucial to ensuring national food security and constructing an ecological civilization. This study is based on the data of 71 prefecture-level cities in the major grain-producing areas in the middle and lower reaches of the Yangtze River from 2008 to 2020. The unit area water resource method, the slacks-based measurement (SBM)-undesirable, the Theil–Sen median analysis, the Mann–Kendall trend test, the coupling coordination degree model, and the spatial autocorrelation model are adopted to measure and analyze the WLRM, the CLUE, and the coupling and coordination level, and their spatial–temporal evolution characteristics quantitatively. Results show the following: (1) From 2008 to 2020, the average value of WLRM in the study areas is 18,200 m3/hm2, which is at a medium level, and the provinces show the characteristics of “high in the south and low in the north, with decreasing gradients”. (2) The annual average of CLUE is 0.777, which is in the medium level, and each province has the remarkable characteristics of “one high and four low”. (3) The coupling coordination degree of WLRM and CLUE is in the primary coordination level, which shows a significant positive correlation in space. In the local perspective, it shows the agglomeration characteristics of “high in the south and low in the north, nodule distribution”. In the future, the neighboring prefecture-level cities should actively build a synergistic mechanism for agricultural development, strengthen the reasonable use of water and land resources and pollution control techniques, drive the transformation of low–low aggregation areas to high–high aggregation areas, and improve the overall coordination of the study areas. This approach aims to promote the construction of ecological civilization and guarantee grain security and sustainable development of agriculture in China.